2008
DOI: 10.1378/chest.07-2146
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Oscillatory Ventilation

Abstract: Background-Instability of breathing control due to heart failure (HF) manifests as exercise oscillatory ventilation (EOV). Prior descriptions of patients with EOV have not been controlled and have been limited to subjects with left ventricular ejection fraction (LVEF) of ≤ 0.40. The aim of this study was to compare clinical characteristics including ventilatory responses of subjects with EOV to those of control subjects with HF matched for LVEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 46 publications
(68 reference statements)
1
19
0
Order By: Relevance
“…19–30%), 3, 68 but it is highly consistent with the prevalence of EOV reported by Sun and colleagues (51%) in a cohort with exercise capacity similar to our HF subjects (peak VO 2 =12 ml/kg/min vs. 12.6 ml/kg/min in our cohort). 5 Like other investigators, we found that EOV was not related to age, gender, or LVEF 7, 29 but was associated with reduced peak VO 2 and a trend toward increased V E /VCO 2 slope. 5, 7, 8 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…19–30%), 3, 68 but it is highly consistent with the prevalence of EOV reported by Sun and colleagues (51%) in a cohort with exercise capacity similar to our HF subjects (peak VO 2 =12 ml/kg/min vs. 12.6 ml/kg/min in our cohort). 5 Like other investigators, we found that EOV was not related to age, gender, or LVEF 7, 29 but was associated with reduced peak VO 2 and a trend toward increased V E /VCO 2 slope. 5, 7, 8 …”
Section: Discussionsupporting
confidence: 83%
“…Ventilatory efficiency (V E /VCO 2 slope) was calculated by previously defined techniques 27 using breath-by-breath data. A subject was considered to have EOV, if they had three or more consecutive, regular oscillations in ventilation (V E ) during exercise, with V E oscillation amplitude ≥ 25% of average V E , 28, 29 persisting for ≥ 60% of exercise duration. 30 Oscillatory cycle length was measured as the average time from nadir-to-nadir for each respective oscillation.…”
Section: Methodsmentioning
confidence: 99%
“…patients commonly respond to exercise with a tachypneic hyperventilation and even occasionally cyclic periodic breathing – the severity of which is prognostic of morbidity and mortality in CHF patients [72, 95]. Deadspace ventilation and V̇E/V̇CO 2 are high owing primarily to the increased breathing frequency but so is V̇ A /V̇CO 2 – thus arterial hypocapnia is common [144].…”
Section: Exercise Hyperpnea In Health and Diseasementioning
confidence: 99%
“…Accordingly, intrathecal fentanyl-induced blockade of muscle afferents in human CHF patients resulted in substantial hypoventilation and CO 2 retention over a wide range of exercise intensities as compared to age matched controls [98]. Thirdly, high pulmonary vascular pressures are common in CHF, especially during exercise and in the presence of pulmonary edema this would precipitate pulmonary C fiber stimulation and a tachypneic ventilatory response and would also be expected to contribute to an unstable, periodic breathing [95, 96]. …”
Section: Exercise Hyperpnea In Health and Diseasementioning
confidence: 99%
“…Exercise oscillatory ventilation is characterized by the regular alternation of hyperpnea and hypopnea during exercise without interposed apnea [1], which distinguished it from other forms of periodic breathing observed in heart failure patients including Cheyne-Stokes respiration or central sleep apnea [2][3][4]. Exercise oscillatory ventilation has been observed in 19-58 % of heart failure patients [5][6][7][8][9][10] and has emerged as a potent independent risk factor for adverse prognosis in heart failure that is additive to traditional echocardiographic and metabolic indices of clinical risk [5,7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%